(untitled) (Swiss Medical Weekly, 2011)
BACKGROUND: Transplantation today faces two major issues: organ shortage, and the increasing age of deceased donors. The former leads to growing waiting lists and, as a consequence, to a higher mortality of patients in need of an organ. The latter results in an augmentation of the proportion of organs from so called extended criteria donors, which, in the past, have been associated with inferior outcomes. METHODS:Retrospective analysis of the patient characteristics of all deceased organ donors in Switzerland from 1 January 1998 to 31 December 2008. A total of 1004 patient records of brain-dead organ donors (59.4% male, 40.6% female) were analysed for demographic data and causes of death. RESULTS:The average donor age increased from 43.8 ± 16.9 years in 1998 to 51.7 ± 18.0 years in 2008 (+27.6%; p <0.05). When comparing 2008 with 1998, cerebral haemorrhage accounts for 52.8% of the causes of death in 2008 (+16.7 percentage points), whereas the proportion of cranio-cerebral trauma decreased by 22 percentage points to 16.9%. The largest group of donors are the 16–55 year-olds with a 50% quota in 2008 (–23.6% compared with 1998). During the study period, the ≥65 year-old group had a 216.2% growth rate, and it accounts 26.6% of the donors in 2008 (p <0.05). CONCLUSIONS: A shift in the causes of death significantly increased the average age of donors, and transplantation medicine is confronted with a growing number of extended criteria donors. Nevertheless, 10-year survival of transplant recipients is better than ever before.